Plasma-Activated Water Against Carbapenem-Resistant Klebsiella pneumoniae and Vancomycin-Resistant Enterococcus faecalis - Dragana Vuković; Maja Miletić; Boško Toljić; Nikola Milojević; Olivera Jovanović; Jovana Kuzmanović Pfićer; Nikola Škoro; Nevena Puač (Pathogens)
The scope of the antibacterial effects of plasma-activated water (PAW) is not yet fully comprehended. We investigated the activity of PAW produced by the in-house 3-pin atmospheric pressure plasma jet against carbapenem-resistant Klebsiella pneumoniae and vancomycin-resistant Enterococcus faecalis, with a focus on PAW’s potential to promote susceptibility to conventional antibiotics in these bacteria. Bacterial inactivation was determined by the colony count after 15 and 60 min PAW treatments. Minimum inhibitory concentrations (MICs) measured following repeated exposures to PAW across multiple generations of bacteria enabled the assessment of changes in susceptibility to antibiotics. The PAW’s efficacy was also analyzed through the detection of intracellular reactive oxygen and nitrogen species in treated bacteria. Time-dependent significant inactivation efficiency against K. pneumoniae was observed (log reduction 6.92 ± 0.24 after 60 min exposure), while effects on E. faecalis were limited. PAW demonstrated potential to decrease the MICs of crucial antibiotics. Namely, a 50 to 62.5% decrease in the MICs of colistin against K. pneumoniae and a 25% reduction in the MICs of vancomycin against enterococci were recorded. We found a significant increase in the superoxide anion concentration in K. pneumoniae and E. faecalis cells after PAW treatments. This study indicates that PAW’s inactivating efficacy coupled with the capacity for the potentiation of antibiotic effects is a promising combination against multidrug-resistant bacteria.